The living, the virtual, and the dead Philippine political figures in online spaces - Serquiña, Oscar Tantoco, Jr (Philippine studies : historical and ethnographic viewpoints, 2019)
"This article examines digital images used during the 2016 Philippine national elections that placed vice presidential candidates Ferdinand "Bongbong" Marcos Jr. and Maria Leonor "Leni" Robredo side-by-side with images of Ferdinand Marcos and Corazon Aquino, respectively. It demonstrates how social networking sites enable the apparitions of dead political figures, whose life stories were deployed for campaign propaganda and political branding. These images were used to profane or sanctify leaders, contrive or rectify popular perceptions, and spawn or shun rhetorical enterprises. These political hauntings may decenter, if not totally change, traditional ways of engaging politics, choosing leaders, and writing histories."